Data for analysis of catechol estrogen metabolites in human plasma by liquid chromatography tandem mass spectrometry - Denver, Nina (Data Brief, 2019)
Analysis of catechol estrogens (2 & 4 hydroxy-estrone and estradiol) has proven troublesome by liquid chromatography tandem mass spectrometry due to their low concentrations, short half-lives and temperature-labile nature. Derivatization to methyl piperazine analogues has been reported for a panel of 9 estrogens in, “Derivatization enhances analysis of estrogens and their bioactive metabolites in human plasma by liquid chromatography tandem mass spectrometry” (Denver et al., 2019). Data show alteration of the base catalyst in this method was required to allow detection of catechol estrogens to low levels. Data also highlight the challenges faced in chromatographic separation of isomers and isotopologues, which were partially overcome by employing an extended column length and reduced oven temperature. In addition, data analysis displayed significant matrix effects during quantitation in plasma, following solid-phase extraction, despite efficient recoveries.